Science and the Trinity : the Christian encounter with reality - Polkinghorne, J. C., 1930-2021. (New Haven : Yale University Press, 2004)
"Most often, the dialogue between religion and science is initiated by the discoveries of modern science - big bang cosmology, evolution, or quantum theory, for example. In this book, scientist-theologian John Polkinghorne changes the discussion. He approaches the dialogue from a little-explored perspective in which theology shapes the argument and sets the agenda of questions to be considered. The author begins with a review of approaches to science and religion in which the classification focuses on theological content rather than on methodological technique. He then proceeds with chapters discussing the role of Scripture, a theology of nature, the doctrine of God, sacramental theology, and eschatology. Throughout, Polkinghorne takes the perspective of Trinitarian thinking while arguing in a style that reflects the influence of his career as a theoretical physicist. In the final chapter, the author defends the appropriateness of addressing issues of science and religion from the specific standpoint of his Christian belief."--Jacket
Four approaches to the dialogue between science and theology -- The role of scripture -- The universe in a Trinitarian perspective : a theology of nature -- Theological thickness -- The Eucharist : liturgy-assisted logic -- Eschatological exploration -- Concluding unscientific postscript : in defence of particularity
Includes bibliographical references and index
Keywords: Religion and science; Trinity; Religion and Science